Aerobic Activation of C‐H Bond in Amines Over a Nanorod Manganese Oxide Catalyst. Issue 1 (26th July 2018) - Wang, Hai; Wang, Liang; Wang, Sai; Dong, Xue; Zhang, Jian; Xiao, Feng‐Shou
Abstract: The development of heterogeneous catalysts for the synthesis of pharmaceutically relevant compounds is always important for chemistry research. Here, we report a selective aerobic oxidation of aromatic and aliphatic amines to corresponding amides over a nanorod manganese oxide (NR‐MnOx ) catalyst. The kinetic studies reveal that the NR‐MnOx catalyzed amine‐to‐amide reaction proceeds the oxidative dehydrogenation of the amines into nitriles, followed by hydrolysis of nitrile into amides. The NR−MnOx exhibits fast kinetics and high selectivities in these steps, as well as hinders the by‐product formation. More importantly, the NR‐MnOx catalyst is stable and reusable in the continuous recycle tests with water as a sole by‐product, exhibiting superior sustainability and significant advancement to outperform the traditional amide production route in acidic or basic media with toxic by‐products. Abstract : Textbook answer ! A sustainable and generalized route for production of amides (up to 21 examples) is developed from selective aerobic oxidations of amines over a non‐noble MnOx nanorod catalyst. More importantly, this catalyst is leaching‐free, stable, and reusable, outperforming the state‐of‐the‐art heterogeneous catalysts such as Ru(OH)x /Al2 O3 .